Tinjauan Yuridis Mengenai Status Keabsahan Kuasa Mutlak atas Terbitnya Kuasa Baru pada Perjanjian - Widjaja, Gunawan; Aisyah, Shyavara (CV. Creative Tugu Pena, 2024)
This research examines in depth the status of the validity of absolute power in the issuance of new power in agreements. The concept of absolute power is often associated with the delegation of unlimited power in an agreement, which can give rise to various legal problems. This research uses a normative juridical approach, by examining statutory regulations, legal theories, and related court decisions. The aim of this research is to evaluate and provide a juridical review of how positive law in Indonesia regulates and views the granting of absolute powers, especially in the issuance of new powers in an agreement. The contribution of this research lies in providing an analysis of the limits and conditions for the validity of absolute powers, as well as the legal implications of the issuance of new powers on the status of the validity of absolute powers in agreements. Keywords: Absolute Power of Attorney Validity Status, New Powers to the Covenant